The importance of economic reforms in the modernization and development of the livestock sector - FAYZIEVA, SHIRIN SHODMONOVNA (The journal of contemporary issues in business and government, 2021)
This article describes the state of the livestock sector in the country, development trends, its importance in the economy, the process of modernization, factors to increase efficiency, the opportunities created, the importance of the adopted reforms.